2006
DOI: 10.1002/pssa.200521475
|View full text |Cite
|
Sign up to set email alerts
|

Optical characterization of polyethylene and cobalt phthalocyanine ultrathin films by means of the ATR technique at surface plasmon resonance

Abstract: It is well known that the development and determination of optical properties of ultrathin films is an important issue in many technological areas. In this work organic polyethylene (PE) and cobalt phthalocyanines (CoPc) ultrathin films were deposited over metal films using the r.f. sputtering and thermal evaporation techniques, respectively. Attenuated total reflection (ATR) measurements for the system organic film/metal at the surface plasmon resonance (SPR) were used for determining the thicknesses and opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…From the theoretical fitting of the SPR reflectivity to the experimental data, as done in Ref. [17], it was found that the dielectric function of the gold film for a 632.8 nm wavelength of the incident light was ε Au = −12.32 + 1.5i and the thickness of the thin polyethylene film was 7.1 nm [17]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the theoretical fitting of the SPR reflectivity to the experimental data, as done in Ref. [17], it was found that the dielectric function of the gold film for a 632.8 nm wavelength of the incident light was ε Au = −12.32 + 1.5i and the thickness of the thin polyethylene film was 7.1 nm [17]. …”
Section: Resultsmentioning
confidence: 99%
“…[17], gold films of 52.4 nm thicknesses were coated on 7059 glass corning substrates by the thermal evaporation method. The commercial monitor MASTEK Inc. , which uses a crystal resonator as a sensor, was used to measure the thickness of the gold films.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 Their optical properties have been studied extensively by different techniques. [16][17][18][19][20][21] However, as shown in Table I, there is a large disagreement in the reported values of e when measured at 632.8 nm. The determination of the thickness of very thin CoPc films (d < 50 nm) is also difficult because the low reflectivity of these materials makes difficult to obtain well defined X-ray interference patterns.…”
Section: Introductionmentioning
confidence: 99%